From manuscript to metadata: preserving Indonesian literary heritage in the contemporary digital transition - M Naveen Kumar; Moh. Ainol Yaqin (Lingua Technica: Journal of Digital Literary Studies, 2026)
Background: The contemporary digital transition has transformed Indonesian literary heritage by shifting literary production from physical manuscripts to born-digital artifacts, while archival infrastructures and metadata practices struggle to keep pace with this change. Objective: This study aims to examine how material transformation, metadata inequality, and digital writing practices collectively reshape literary preservation and authorship in Indonesia. Method: Using a qualitative interpretive approach grounded in digital humanities and archival studies, the research analyzes a multi-layered corpus comprising institutional archives, author-managed digital materials, and platform-based literary outputs through comparative archival analysis and visual-analytic mapping. Results: The findings reveal three interrelated patterns: a dominance of born-digital literary materials accompanied by low archival stability, a stratified metadata landscape that privileges institutional archives over platform-based environments, and a structural tension between high textual productivity and fragile preservation in digital authorship practices. Implication: These patterns indicate that digital literary abundance does not guarantee cultural memory without coordinated archival mediation. Novelty: This study introduces a visual–relational framework that reframes Indonesian literary heritage as an infrastructural and authorially contingent process within the digital transition.